Analisis Pengaruh Keselamatan dan Kesehatan Kerja Terhadap Risiko Kecelakaan Kerja Menggunakan Metode Failure Mode Effect and Analysispada 888 Plast - Rizky Yunus Karnadi (Jurnal Serambi Engineering, 2024)
This research aims to determine the effect of implementing Occupational Safety and Health (K3) on the risk of work accidents. The respondents of this research were 16 people who were warehouse and production employees. The data sources used are primary and secondary data. The analytical method used inthis research is Failure Mode and Effect Analysis (FMEA) which is processed with Microsoft Excel. The research results show that there is a significant influence on the implementation of K3 because the root cause of work accidents is caused by the lack ofuse and application of available K3 facilities, such as shoes, air ventilation and socialization. From data processing using the Failure Mode and Effect Analysis (FMEA) method, it is known that there are 3 types of work accidents that have high RPN values, namely cuts by cutters with an RPN value of 45, exposure to scissors with an RPN value of 45, and exposure to machine heat with an RPN value of 40. There are The four main factors that influence problems are humans, management, work methods, and work environment.